2016
DOI: 10.1016/j.ymgme.2015.09.012
|View full text |Cite
|
Sign up to set email alerts
|

A beta-blocker, propranolol, decreases the efficacy from enzyme replacement therapy in Pompe disease

Abstract: Enzyme replacement therapy (ERT) with recombinant human acid α-glucosidase (rhGAA) fails to completely reverse muscle weakness in Pompe disease. β2-agonists enhanced ERT by increasing receptor-mediated uptake of rhGAA in skeletal muscles. Purpose To test the hypothesis that a β-blocker might reduce the efficacy of ERT, because the action of β-blockers opposes those of β2-agonists. Methods Mice with Pompe disease were treated with propranolol (a β-blocker) or clenbuterol in combination with ERT, or with ERT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
2
9
0
1
Order By: Relevance
“…4B). Furthermore, administration of propranolol, a beta-blocker that increased the uptake of GAA but reduced efficacy from ERT [16], failed to reduce LC3-II (Fig. 4A,C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4B). Furthermore, administration of propranolol, a beta-blocker that increased the uptake of GAA but reduced efficacy from ERT [16], failed to reduce LC3-II (Fig. 4A,C).…”
Section: Resultsmentioning
confidence: 99%
“…However, this phenomenon has been observed following administration of ERT with propranolol [16]. The observed improvement in muscle function might be attributable to greater cardiac function following biochemical correction of the heart, although cardiac function was not directly evaluated in either of these studies.…”
Section: Discussionmentioning
confidence: 97%
“…Beta-2 adrenergic agonists, most notably albuterol, have been used to increase muscle mass and strength in normal individuals and in patients with muscular dystrophy [9] , [10] . Beta-2 agonists were demonstrated to increase the expression of cation-independent mannose-6-phosphate receptor (CI-MPR) and CI-MPR-mediated uptake of rhGAA in murine Pompe disease [11] , and beta-blockers decreased the efficacy of rhGAA therapy [12] . A pilot clinical trial also showed improvement in muscle power in a 6-minute walk test (6MWT) in adult patients with LOPD [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Decreased glycogen content has correlated with lower ventricle mass in treated GAA-KO mice 18 . Left ventricle mass was significantly decreased by administration of 3E+9 vg in comparison with PBS-injected controls (Figure 3C), both in groups of mice treated as infants (p < 0.001) and as adults (p < 0.001).…”
Section: Resultsmentioning
confidence: 88%